Research trend of emotional intelligence in biology learning: A bibliometric analysis in the last ten year - Bimo Aji Nugroho; Hery Fajeriadi; Much. Fuad Saifuddin (UNIVERSITAS LAMBUNG MANGKURAT, 2025)
Research that explicitly examines emotional intelligence (EI) in biology learning is still limited, even though extensive evidence shows that EI supports motivation, interaction quality, and learning effectiveness, which are relevant competencies in collaborative tasks and complex biology practicums. This study analyzes research trends and opportunities related to emotional intelligence in biology learning (EIBL) through a bibliometric approach. A literature-based bibliometric analysis was conducted using 339 screened documents retrieved from the ScienceDirect (2015-2024), and the dataset was visualized using VOSviewer to map publication distribution, subject areas, publisher sources, and keyword networks. The findings indicate an increasing number of publications, dominance of empirical studies, and multidisciplinary dissemination across psychology, education, biomedicine, and social sciences. Network visualization identified five thematic clusters (research challenges, methodological approaches, educational contexts, emotional-systemic aspects, and developmental issues) reflecting broader patterns in the dataset rather than trends specific to biology learning. Overall, the dataset suggests emerging opportunities for integrating emotional intelligence into biology learning practices, while highlighting the limited number of studies explicitly situated in biology education and the need for further empirical exploration.Abstrak. Penelitian yang secara eksplisit mengkaji kecerdasan emosional (EI) dalam pembelajaran biologi masih terbatas, meskipun bukti luas menunjukkan bahwa EI mendukung motivasi, kualitas interaksi, dan efektivitas belajar, yaitu kompetensi penting dalam tugas kolaboratif dan praktikum biologi yang kompleks. Penelitian ini menganalisis tren dan peluang penelitian emotional intelligence in biology learning (EIBL) melalui pendekatan bibliometrik. Analisis bibliometrik berbasis literatur dilakukan menggunakan 339 dokumen hasil penyaringan dari ScienceDirect (2015-2024), dan dataset ini divisualisasikan menggunakan VOSviewer untuk memetakan sebaran publikasi, subject area, sumber penerbit, serta jejaring kata kunci. Hasil analisis menunjukkan peningkatan jumlah publikasi, dominasi artikel empiris, dan penyebaran multidisipliner pada bidang psikologi, pendidikan, biomedis, dan ilmu sosial. Visualisasi jaringan mengidentifikasi lima kluster tema (tantangan penelitian, pendekatan metodologis, konteks pendidikan, aspek emosional-sistemik, dan isu perkembangan) yang mencerminkan pola umum dalam dataset, bukan tren spesifik pembelajaran biologi. Secara keseluruhan, dataset menunjukkan peluang berkembangnya integrasi kecerdasan emosional dalam praktik pembelajaran biologi, sekaligus menegaskan terbatasnya studi yang secara eksplisit berada dalam konteks biologi serta kebutuhan eksplorasi empiris lanjutan.